IMRT improves local control in patients with nasopharyngeal carcinoma compared with conventional radiotherapy: propensity score-matched analysis. (12th July 2021) - Ma, Zichang; Umezawa, Rei; Yamamoto, Takaya; Ishikawa, Yojiro; Takahashi, Noriyoshi; Takeda, Kazuya; Suzuki, Yu; Tang, Liuwei; Ito, Kengo; Kadoya, Noriyuki; Jingu, Keiichi
Abstract: Background: It is still controversial whether intensity-modulated radiotherapy has an obvious advantage over conventional radiotherapy. The purposes of this study were to evaluate prognostic factors in pre-treatment characteristics for nasopharyngeal carcinoma and to compare treatment outcomes in patients who received intensity-modulated radiotherapy and patients who received two-dimensional radiotherapy or three-dimensional radiotherapy. Methods: We reviewed patients with nasopharyngeal carcinoma who received chemoradiotherapy in our hospital during the period from 2000 to 2017, and we excluded patients who had a history of surgery for nasopharyngeal carcinoma and those who had distant metastases before treatment. A total of 72 patients who were treated by radiotherapy with concurrent chemotherapy were enrolled. All of the patients were irradiated with a total dose of 58–70 Gy. Overall survival, locoregional control and progression-free survival rates were compared in the groups treated by intensity-modulated radiotherapy and two-dimensional/three-dimensional radiotherapy. Propensity score matching was performed to homogenize the two groups. Results: The median follow-up period was 62.5 months. After propensity score matching, in patients treated with intensity-modulated radiotherapy, the 5-year rate of overall survival, locoregional control and progression-free survival were 73.5, 95.2 and 72.7%, respectively. In patients treated with two-dimensional/three-dimensional radiotherapy, the 5-year rate of overall survival, locoregional control and progression-free survival were 69.1, 67.7 and 51.8%, respectively. There was a significant difference between the groups only in locoregional control. Late toxicities of grade 2 or higher were occurred in 38.5 and 24.2% of the patients treated by two-dimensional/three-dimensional radiotherapy and intensity-modulated radiotherapy, respectively. Conclusions: Our results suggested that intensity-modulated radiotherapy is more effective than two-dimensional/three-dimensional radiotherapy in patients with nasopharyngeal carcinoma, especially in locoregional control. Abstract : Intensity-modulated radiotherapy improves local control in patients with nasopharyngeal carcinoma with long follow-up by using propensity score-matched analysis compared with two-dimensional/three-dimensional radiotherapy.